RECONSTRUCTION OF MODERATE ISLAMIC THEOLOGICAL REASON; AS SOLUTION FACING THE NEW NORMAL TIME FOR YOUTH MUHAMMADIYAH AT THE LEADERS OF THE YOUTH MUHAMMADIYAH BRANCH MEDAN BARU, MEDAN CITY - Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2022)
This service aims to reconstruction of moderate Islamic theological reasoning among Muhammadiyah youths in as solution facing the new normal outbreak in the Leadership of the Youth Muhammadiyah At The Leaders Of The Youth Muhammadiyah Branch Medan Baru Medan City. This needs to be done so that Muslim youth as agents of change in people's lives can become figures who have a high level of awareness related to the Covid-19 outbreak. Breaking the chain of the spread of Covid-19 really requires the role of all parties, including youth. Therefore, it is necessary to strengthen understanding in addressing the dangers of Covid-19 by approaching moderate religious values (washattiyah) as part of reasoning activities. The theological reasoning built in responding to Covid-19 among youth is by providing an understanding of how Islam responds to the conditions of an outbreak, in this case Covid-19. This includes providing an understanding to comply with Health protocols which are also part of Islamic values.Keyword: Reconstruction, Theology, Moderate Islam, Muhammadiyah Youth